6 - Understanding the Factors that Influence Leadership Effectiveness of Deans in Ghana - Goski Alabi,; Joshua Alabi, (Journal of Higher Education in Africa, 2014)
The paper describes and examines the factors that influence leadership effectiveness of deans and the concept of competence of deans using the evolution of deanship as a welfare system to a system of accountability in Ghana. The study explores what defines leadership competence in Higher Education in Ghana and how the process of becoming a dean can influence effective performance. Using a qualitative approach, data was collected from 38 respon Three public Universities in Ghana were used for the stu- dy. Data was collected from 38 respondents using interviews and survey methods. The respondents include a vice-chancellor, a pro-vice-chancellor, deans, and faculty members. The paper explores the respondents’ perception of a competent dean and identifies two categories of competence: technical competence and leadership competence. Generally, leadership competences are put ahead of technical competences for effective deans’ performace. Five core themes for leadership competences were identified and these include personal competences, visionary competences, administrative competences, people competences and networking competences. Also, three processes of becoming a dean have also emerged in Ghana. These are the elective, the selective and the appointive processes. The study finds that the effectiveness of deans is largely influenced by inadequate leadership competences and grooming, absence of clearly defined and well commu- nicated job descriptions as well as performance management practices that seek accountability of deans in Ghana. The study recommends the appointment of deans through standard recruitment practices, rather than election or selection. It also recommends leadership assessment and training for leadership competences before a dean takes office.